Prediction of atherosclerosis in peripheral arterial disease using computational fluid dynamics modelling - Ukasyah Zulfaqar, Shahrulakmar; Nasrul Hadi, Johari; Juhara, Haron; Nadarajan, Chandran; Mohd Nadzeri, Omar (Springer, 2024)
Peripheral arterial disease (PAD) is a type of cardiovascular disease (CVD) that impacts the blood arteries in the body's lower extremities. It is distinguished by the development of plaque in the arterial wall because of fat, cholesterol, and other material buildup. The objective of this research is to establish computational fluid dynamics (CFD) models for recognizing potential regions for atherosclerosis to arise in the peripheral artery and its impact after occurrence. changes and effects in healthy and stenotic arteries using computational analysis. Two peripheral artery models, healthy and stenosed, were constructed. The stenosis structure is constructed based on a trapezoidal shape. In healthy peripheral phantom geometry, the location of stenotic was identified by preliminary flow analysis. Subsequently, the reconstructed geometry of the PAD model was exported to ANSYS-Workbench for mesh generation. Laminar blood flows consideration was simulated by numerically solving the governing equations for an incompressible fluid using finite volume-based computational fluid dynamics (CFD). The velocity and wall shear stress (WSS) profile of healthy peripheral arteries were analyzed to investigate the flow behavior and potential region to occur atherosclerosis. The results showed that there is a significant change in the velocity distribution with the presence of stenosis at the branching of the profunda and SFA. The computational analysis also helps to understand in depth the influence of flow patterns on blood flow in the peripheral artery. Thus, CFD simulations can provide a better understanding of the underlying fluid mechanics and the role of fluid dynamics in the disease processes.